If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2 = 3(y + -5) Reorder the terms: 2 + 4y = 3(y + -5) Reorder the terms: 2 + 4y = 3(-5 + y) 2 + 4y = (-5 * 3 + y * 3) 2 + 4y = (-15 + 3y) Solving 2 + 4y = -15 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 2 + 4y + -3y = -15 + 3y + -3y Combine like terms: 4y + -3y = 1y 2 + 1y = -15 + 3y + -3y Combine like terms: 3y + -3y = 0 2 + 1y = -15 + 0 2 + 1y = -15 Add '-2' to each side of the equation. 2 + -2 + 1y = -15 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = -15 + -2 1y = -15 + -2 Combine like terms: -15 + -2 = -17 1y = -17 Divide each side by '1'. y = -17 Simplifying y = -17
| 3(3+3x)=8(x-2) | | 3(3+3)=8(x-2) | | 6x/2-3 | | 7*7*7*7*7=212 | | 7*5=212 | | 3t-9=7-1 | | 6x+3y=15.75 | | 7z-5-5(z+1)=-(4z+7) | | 1/3*4x | | 2k^2+7k-30=0 | | 7-q/4=2.5 | | 7-4=2.5 | | -3x+10y=0 | | sx+ty=ufory | | 8v=-18 | | 4lnx+6=0 | | 7(x+2)-8(4+3x)=47 | | 7(x-2)-8(4+3x)=47 | | 9x^2-100x+1000=0 | | 4x-t=14 | | (9-3g)-(3+12g)= | | log(x-1)-log(x+1)-log(8)=-2 | | 2x-7y+z=-5 | | x^3+4x^2+60x-17=0 | | log(x-1)-2*log(x+1)-log(8)=-2 | | x+2x+2=2 | | -3=57+(n+1)-4 | | -3m(m-10)=0 | | 5x-7=3(x+3) | | -3x=40000 | | 5x-11=2(x+14) | | 40-8x=32 |